Amphibious Subjects Sasso and the Contested Politics of Queer Self-Making in Neoliberal Ghana - Otu, Kwame Edwin (University of California Press, 2022)
Amphibious Subjects is an ethnographic study of a community of self-identified effeminate men- known in local parlance as sasso-residing in coastal Jamestown, a suburb of Accra, Ghana's capital. Drawing on the Ghanaian philosopher Kwame Gyekye's notion of "amphibious personhood," Kwame Edwin Otu argues that sasso embody and articulate amphibious subjectivity in their self-making, creating an identity that moves beyond the homogenizing impulses of Western categories of gender and sexuality. Such subjectivity unsettles claims made by both the Christian heteronationalist state and LGBT+ human rights organizations that Ghana is predominantly heterosexual or homophobic. Weaving together personal interactions with sasso, participant observation, autoethnography, archival sources, essays from African and African-diasporic literature, and critical analyses of documentaries such as the BBC's The World's Worst Place to Be Gay, Amphibious Subjects is an ethnographic meditation on how Africa is configured as the "heart of homophobic darkness" in transnational LGBT+ human rights imaginaries. "This book is a powerful synthesis of African theorization and rigorous fieldwork that presents an engaging and convincing read of a location. Kwame Edwin Otu's work is not simply meaningful for Jamestown, Accra, Ghana, or West Africa; it has real import elsewhere while remaining committed to its locality and subjects, a rare feat." T. J. Tallie, author of Queering Colonial Natal: Indigeneity and the Violence of Belonging in Southern Africa "A unique project based on groundbreaking research. There is no other work that gives such elegant insight into the multifarious desires of queer life-in an African city or anywhere. Otu convincingly shows how simplistic identity categories are confounded by the fluidities and illegibilities of lived queer experience." Jesse Weaver Shipley, Professor of African and African American Studies and Oratory, Dartmouth College